2021
DOI: 10.35814/jifi.v19i1.842
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan Laju Difusi Allisin dalam Sistem Fitosom Ekstrak Bawang Putih

Abstract: Garlic (Allium sativum L.) contains allicin, which has the biological activity of reducing blood sugar levels. The results of previous studies stated that the methanol extract of garlic was able to reduce blood sugar levels in mice with a dose of 400 mg/kg BW. Allicin permeability of extract can be increased by formulating it into the phytosome system. The objective of this study is to determine the eff ect of allicin loaded phytosome on the diff usion rate of allicin. Garlic extract phytosome was made using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Other research has also shown that 246.1 nm of phytosome evodiamine played a significant role in the sustained release and enhancement of evodiamine's oral absorption efficiency [42]. In another study, phytosomes of garlic extract had a particle size of 270 nm, indicating that the rate of diffusion of allicin was greater than in the form of extract alone [43]. Based on the particle size, the phytosome of garlic extract was appropriate for oral and topical drug delivery.…”
Section: Discussionmentioning
confidence: 94%
“…Other research has also shown that 246.1 nm of phytosome evodiamine played a significant role in the sustained release and enhancement of evodiamine's oral absorption efficiency [42]. In another study, phytosomes of garlic extract had a particle size of 270 nm, indicating that the rate of diffusion of allicin was greater than in the form of extract alone [43]. Based on the particle size, the phytosome of garlic extract was appropriate for oral and topical drug delivery.…”
Section: Discussionmentioning
confidence: 94%